Biomimetic heart platforms for drug development - Sungwoo Cho; Sungho Ko (Organoid, 2022)
New drug development is currently very expensive and time-consuming. In addition, some drugs that are approved after animal and clinical trials have their approval revoked because of adverse effects. About 30% of such drugs have heart side effects. Conventional cell-based drug toxicity tests are performed under conditions entirely different from the in vivo environment, and animal testing for drug evaluation has limitations because of differences between species. Therefore, researchers are increasingly focusing on developing models that can overcome these limitations to enable accurate drug toxicity tests. This review outlines biomimetic in vitro heart platforms, such as heart organoids, 3-dimensional bioprinting, and heart-on-a-chip devices, and describes their advantages, limitations, future perspectives. The development and use of effective cardiac biomimetic models could contribute to the development of alternatives to animal testing by providing more specific information on drug metabolism and reducing the rate of failure in later stages of drug development.